The Effect of Educational Media Website and Surveillance on Risk Behavior for Prevention of Premarital Sex and Sexual Violence in Adolescents in Gorontalo Regency High School - L.Z. Ngabito, Siti Maryam; Wahiduddin,; Maria, Ida Leida; Amiruddin, Ridwan; Nasir, Sudirman; Citrakesumasari, (International Journal of Statistics in Medical Research, 2024)
Objective: This study aims to assess the effect of website media and surveillance on risk behaviors to prevent premarital sex and sexual violence among high school adolescents in Gorontalo Regency. Materials and Methods: Quasi-experimental research with non-equivalent control group design. Involving 158 adolescent students who were divided into two, namely the intervention group was given education through the Si Waspada Diri website media and the control group was given G'sites, both of which contained material modified from the Comprehensive Sexuality and Reproductive Health Education (CSHE) guidelines. The sampling technique was proportional systematic random sampling with sample criteria aged 15-18 years who were already dating. The research instrument was a knowledge, attitude and practice questionnaire that had previously been tested for validity and reliability Results: Knowledge, attitudes and practices of preventing premarital sex and sexual violence were significantly better using the Si Waspada Diri website and G'Sites. With a p value of less than 0.005, the mean difference after education showed that using the website was more beneficial than using G'Sites in terms of knowledge and attitude. In addition, for practices, p = 1.000 showed no significant difference between the two groups. Conclusion: Comprehensive sexual and reproductive health education materials such as Si Waspada Diri websites and G'sites help lower teenage sexual behavior practices, promote good attitudes, and raise awareness. Nonetheless, G'sites are less successful than websites in raising awareness and attitudes.